(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article attempts to study the psychological aspects of using new technologies and innovations in the education system. It analyzes how modern technologies affect the educational process, how they affect students’ motivation, attention, memory and creative abilities. It also examines the psychological readiness of teachers to master new technologies and their impact on the quality of education. The article provides recommendations on ways to improve the psychological state of students and increase the effectiveness of education through the correct use of technologies in education.